Preparation and characterization of rice starch based solid polymer electrolytes for dye−sensitized solar cell application / Mohammad Hassan Khanmirzaei - Khanmirzaei, Mohammad Hassan (2015)

(untitled)
Biodegradable polymers have economic and environmental benefits due to cheap in cost and biodegradability. Utilizing environmental friendly polymers in polymer electrolytes and electronics field can be good replacement for some harmful existing materials and admirable category for green energy applications such as solar cells, specifically, dye sensitized solar cells, super capacitors, batteries, etc. Solid polymer electrolyte (SPE) systems based on rice starch as a biodegradable polymer, three iodide salts namely lithium iodide, ammonium iodide and sodium iodide, and two ionic liquids namely 1-methyl-3-propylimidazolium iodide (MPII) and 1-hexyl-3-methylimidazolium iodide (HMII) were studied for dielectric properties and solar cell applications in this research. Polymer electrolytes were prepared using solution cast technique. The ionic conductivity and temperature-dependent conductivity and dielectric behavior were analyzed in this work. The highest ionic conductivities were achieved in SPE systems after addition of ionic liquid. The solid polymer electrolytes were characterized for dielectric, structural and thermal properties using EIS, FTIR, XRD, TGA and DSC. In temperature-dependent study, all SPEs follow the Arrhenius thermal activated model. In structural study using FTIR and XRD, complexations between polymer, salt and ionic liquid were confirmed for all SPEs. Furthermore, Thermal studies using TGA and DSC thermograms demonstrated that decomposition temperature (Tdc) and glass transition temperature (Tg) for rice starch shift upon complexation with iodide salt and ionic liquid. Dye sensitized solar cells (DSSCs) were fabricated using SPE systems with highest ionic conductivities. TiO2 paste was doctor-bladed on FTO substrate and sintered at 450 ℃ as photo-electrode. The photo-electrode was immersed in Ruthenium based dye (N719) for 24 hr. Platinum coated FTO was used as the counter electrode. iv Solid polymer electrolytes were sandwiched between two photo and counter electrode with the configuration of Glass/FTO/TiO2/N719-Dye/Solid polymer electrolyte/Pt/FTO/Glass. The fabricated DSSCs were analyzed for energy conversion using Sun simulator with white light illumination of 1000 (W m−2) defined as incident light power. The DSSCs show significant conversion energy efficiencies for solid biopolymer based solar cells as green energy source.